PROPOSAL OF A RAO RIDGE TYPE ESTIMATOR - COSTA, Luzia Aparecida (2018)
Based on a geometrical interpretation of Ridge estimators a new Rao Ridge type estimator is proposed. Its advantage is to reach the optimum value for the shrinkage parameter more quickly. The geometry, the predictive capacity, a computational example, an application to real data and comparison with the usual Ridge estimator are developed.